Reliability and variability of running economy in elite distance runners - Saunders, P. U.; Pyne, D. B.; Telford, R. D.; Hawley, J. A. (Medicine & Science in Sports & Exercise, 2003)
Purpose: To establish the typical error (TE) associated with equipment, testing, and biological variation of a running economy (RE) test in 11 elite male distance runners ([latin capital V with dot above]O2max 70.3 +/- 7.3 mL[middle dot]min-1[middle dot]kg-1), and measure the between-athlete variation of 70 highly trained runners ([latin capital V with dot above]O2max 69.7 +/- 6.0 mL[middle dot]min-1[middle dot]kg-1) to determine the magnitude of the smallest worthwhile change (SWC) required for RE.